A Synchronous Diagnosis of Metastatic Male Breast Cancer and Prostate Cancer. (May 2019) - Moosavi, Leila; Kim, Phyllis; Uche, An; Cobos, Everardo
In this article, we present a patient diagnosed synchronously with metastatic male breast cancer and prostate cancer. This is a 63-year-old male and recent immigrant from Nigeria, who sought medical attention for progressively worsening of shortness of breath and acute progression of a chronic right breast mass. An invasive breast carcinoma was diagnosed by the core biopsy of the right breast mass. Within 2 months of his breast cancer diagnosis, the patient also was diagnosed with prostate adenocarcinoma after being worked up for urinary retention. By presenting this patient with a synchronous diagnosis with metastatic male breast cancer and prostate cancer, history of chronic right breast mass, and gynecomastia, we speculate on possible cancer etiologies and risk factors.